(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Questions were asked about preference for eating dried meats produced from raw meats of cattle, sheep, goat and camel. Evaluation of consumption liking by colour, flavor, overall desirability and percentage of consumer choice was carried out from 145 panelists who live in Ulaanbaatar. In results, low score in colour, flavor and overall desirability was shown in order for dried meats from cattle, goat, sheep and camel. According this result, consumer choice was high (90%) in dried meat from cattle, while theconcentrate (50%) was low in dried meat from camel and sheep. Dried meat from cattle and goat had the lowest TBARS value, followed by mutton and camel meat in that order. In conclusion, dried meat from cattle had the highest scores for the three characteristics and low value in lipid oxidation products. Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 3-9